Calendar Anomalies in Indian Stock Market - Choudhary, Dr. Kapil (Indian Journal of Finance, 2007)
Till the late seventies, empirical studies bolstered the view that capital market are informational efficient. Academician and researcher on the concept of informational efficiency of capital markets developed various theoretical security valuation models. However the late seventies and eighties produced the evidences questioning the validity of this theory and illuminated the various anomalies related to the capital market efficiency. These studies demonstrated the possible trading strategies, seasonal anomalies and persistence of technical analysis yielding abnormal returns using the historical data and publicly available information. Studies on the Indian stock market's calendar anomalies, especially in the recent bull phase of market due to growing economy, wider participation foreign institutional investors and retail investors, are very few. In an attempt to fill this gap, this study explores the Indian stock market's informational efficiency in its weak form in the context of calendar anomalies especially in respect of the day of week effect and month of the year effect. In this attempt to find seasonality in Indian stock market the study used the daily closing value of BSE Sensex and BSE 100 indices for the period during January 1996 to December 2006. The study is bifurcated into two sub-periods. One important thing that distinguished this study from earlier studies is that it incorporated both the parametric and non-parametric approach to check any seasonal pattern in common stock returns. The findings regarding the day of the week reported no significant differences in sample distribution of daily common stock returns during the whole study period and second sub-period (2002-2006). It is curious to note the empirical findings reported the day of the week effect during the first study period (1996-2001). Regarding the month of the year effect the study has not reported any anomaly regarding the average monthly return during the whole study period and first sub-period (1996-2001). In the second sub-period (2002-2006) the study exhibited evidences in favor of alternative hypothesis that the average monthly returns are not equal. The study adds to existing market efficiency literature that both the parametric and non-parametric approaches yield similar results regarding examination of seasonality in common stock return.